مراقبة بعض الأدوية الفيتامينية الوطنية والمهربة الموجودة في السوق المحلية - ياسين مفيد; هارون محمد; إسماعيل غنوة (Latakia University Journal -Medical Sciences Series, 2019)
تعد مشكلة الدواء المهرب من أخطر المشاكل الاقتصادية والصحية التي تواجهها البلدان، وظاهرة انتشار الدواء المهرب والمزور ليست محصورة بحدود، وإنما انتشرت بالعالم ككل وسورية ليست في منأى عنها، لذلك كان من الضروري معرفة الأسباب وراء انتشار هذه الظاهرة وذلك من خلال مراقبة جودة بعض الأدوية المصنعة محليا والمهربة للوصول إلى الإجابة. تم في هذا البحث دراسة مجموعة من المستحضرات التجارية لفيتامينات منحلة في الماء (B Complex ,C) بشكل مضغوطات وذلك لأنها من الأصناف المتواجدة بكثرة والتي تباع في الصيدليات دون وصفة طبية. شملت الدراسة فحوص الشكل الخارجي ولصاقة التوسيم وفحوص تجانس الوزن والقساوة والهشاشة والتفتت ومحتوى المادة الفعالة وذلك باستخدام الأجهزة الخاصة بهذه الفحوص, وذلك وفقا لما تتطلبه الدساتير الدوائية وباستخدام طرق تحليلية معتمدة. بينت النتائج مطابقة جميع الأشكال الوطنية للمواصفات الدستورية فيما يتعلق بفحوص الغلاف الخارجي وتجانس الوزن والتفتت وكذلك فحص محتوى المادة الفعالة من حيث مطابقتها للجرعة المذكورة على الغلاف الخارجي للعبوة، أما بالنسبة للأشكال المهربة فتم دراسة شكل يحوي فيتامينC وشكل يحوي فيتامين B6 وشكل ثالث يحوي مجموعة فيتامينات B (B1, B6, B12 ), وكان شكل واحد فقط من هذه الأشكال مطابقاً للمواصفات الدستورية في حين خالفت باقي الأشكال (مضغوطات فيتامين C الفوارة, مضغوطات فيتامينات B1,B6,B12) المواصفات الدستورية فيما يخص الغلاف الخارجي ودراسة الخصائص الميكانيكية وكذلك محتوى المادة الفعالة, وبالتالي فإن الدواء المهرب غير آمن الاستخدام. The problem of the smuggled drug is one of the most serious economic and healthy problems that countries face. The phenomenon of spreading the smuggled and counterfeited drugs is not confined to any limits, but it has spread the whole world and Syria is not far from it. So, it was necessary to know the reasons behind the spread of such a phenomenon through overseeing the quality of certain drugs which are manufactured locally and those trafficked to strike an answer. This study examines many water-soluble vitamins (B complex, C) in tablets because they had a lot of varieties which are sold in pharmacies without a prescription. In this work, we have studied some dosage forms (tablets) of water – soluble vitamins (B6, B12 and C). The aim of the study was to compare some local vitamin drugs with trafficked and legal ones. The study included the tests of exterior label and labeling as well as, the tests of weight uniformity, hardness, friability, disintegration, dissolution, and the content of uniformity tests in accordance with the requirements of the pharmacopeias and constitutions. The results revealed that all national dosage forms conform to the pharmacopoeia specifications. For the trafficked drugs, one was conformed to the compendia requirements, while the others, (C effervescent tablets, B1, B6, B12 vitamin tablets) were not conformed to exterior label, mechanical merits and content uniformity. These results indicated that trafficked drugs are not safe for the patients.